2015
DOI: 10.7554/elife.05981
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal threonines and serines play distinct roles in the desensitization of rhodopsin, a G protein-coupled receptor

Abstract: Rod photoreceptors generate measurable responses to single-photon activation of individual molecules of the G protein-coupled receptor (GPCR), rhodopsin. Timely rhodopsin desensitization depends on phosphorylation and arrestin binding, which quenches G protein activation. Rhodopsin phosphorylation has been measured biochemically at C-terminal serine residues, suggesting that these residues are critical for producing fast, low-noise responses. The role of native threonine residues is unclear. We compared single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…Indeed, similar rhodopsin mutants with single or multiple serine/threonine residues substituted with alanine have been reported to prolong reproducible single-photon response, i.e. rhodopsin deactivation and recovery (Azevedo et al, 2015; Mendez et al, 2000). We further tested the effects of the phosphorylation code of V2R C-tail on arrestin binding by mutations of S357A/T360A/S363A (3A) or S357A/T360A/S362A/S363A/S364A (6A) that respectively disrupt either the first phosphorylation code SCTTAS or both codes SCTTAS and SCTTASS on the V2R C-tail of a β 2 AR-V2R chimeric receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, similar rhodopsin mutants with single or multiple serine/threonine residues substituted with alanine have been reported to prolong reproducible single-photon response, i.e. rhodopsin deactivation and recovery (Azevedo et al, 2015; Mendez et al, 2000). We further tested the effects of the phosphorylation code of V2R C-tail on arrestin binding by mutations of S357A/T360A/S363A (3A) or S357A/T360A/S362A/S363A/S364A (6A) that respectively disrupt either the first phosphorylation code SCTTAS or both codes SCTTAS and SCTTASS on the V2R C-tail of a β 2 AR-V2R chimeric receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Although arrestin binds poorly to singly phosphorylated Rh*, it can bind almost fully when already three of the six sites are phosphorylated . Sites are probably not phosphorylated at random, because Kennedy and coworkers have shown that serines are among the first to be phosphorylated , whereas the recent results of Azevedo and coworkers indicate that phosphorylation of threonines is especially important for terminating Rh* activity. Despite clever and determined attempts by many investigators, we still do not know the specificity of the kinase or time course of its action.…”
Section: Single‐photon Responses Are Surprisingly Constant In Amplitudementioning
confidence: 99%
“…We have seen above how rhodopsin, by its funnel-like interaction process, can manage to interact with its signaling proteins both fast and precisely. The catalytic process lasts until R* becomes deactivated, generating a surprisingly uniform single quantum response (see Azevedo et al, 2015). Current estimates of R* lifetime in mouse rods are in the range of ∼40 milliseconds (Gross and Burns, 2010).…”
Section: Temporal Aspects-kinetics Along the Signaling Chainmentioning
confidence: 99%